2022
DOI: 10.14202/vetworld.2022.1185-1190
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and antibiogram of multidrug-resistant Salmonella enterica isolated from dairy products in Libya

Abstract: Background and Aim: Foodborne illnesses are a serious challenge to human health and the economic sector. For example, salmonellosis remains a burden in developed and developing nations. Rapid and reliable molecular methods to identify Salmonella strains are essential for minimizing human infection. This study aimed to identify Salmonella spp. in raw milk and dairy products using conventional and molecular techniques and to test the antibiotic susceptibility of the isolated strains. Materials and Methods: One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Of the 80 bacteria isolated, 52/80 (65.0%) were MDRs and 20/49 (40.8%) isolates were confirmed as ESBL producers. Previous studies conducted in different parts of the world reported increased levels of MDR 5,[55][56][57][58][59][60][61][62][63][64] and ESBL-producing bacteria. [65][66][67][68][69] The higher levels of resistance observed in this study may be due to inappropriate antibiotic use on dairy farms.…”
Section: Dovepressmentioning
confidence: 86%
“…Of the 80 bacteria isolated, 52/80 (65.0%) were MDRs and 20/49 (40.8%) isolates were confirmed as ESBL producers. Previous studies conducted in different parts of the world reported increased levels of MDR 5,[55][56][57][58][59][60][61][62][63][64] and ESBL-producing bacteria. [65][66][67][68][69] The higher levels of resistance observed in this study may be due to inappropriate antibiotic use on dairy farms.…”
Section: Dovepressmentioning
confidence: 86%
“…E. coli, Cronobacter spp., and Salmonella enterica have previously been reported by Garbaj et al [15], Garbaj et al [16] and Garbaj et al [17] as foodborne pathogens associated with dairy products in Libya. Data on the microbiological quality of Libyan dairy products related to K. pneumoniae are lacking.…”
Section: Introductionmentioning
confidence: 82%
“…[ 15 ], Garbaj et al . [ 16 ] and Garbaj et al . [ 17 ] as foodborne pathogens associated with dairy products in Libya.…”
Section: Introductionmentioning
confidence: 99%
“…Abbassi et al [76] showed 57% amoxicillin resistance to E. coli in livestock in Tunisia, whereas 95% was found in diarrheal calves in Chile [77]. On the other hand, Garbaj et al [78] found 100% Salmonella-resistant amoxicillin in dairy products in Libya. Fig.…”
Section: Pattern Of Amoxicillin Resistance In Bangladeshmentioning
confidence: 99%